DIFFERENCES IN CHANGES IN KNOWLEDGE OF WOMEN ABOUT EARLY DETECTION OF CERVICAL CANCER BETWEEN USING PRESENTATION MEDIA COUNSELING AND LEAFLET COUNSELING - Yuliana, Baiq Ade Herna; Purwanto , Bambang; Euvanggelia Dwilda Ferdinandus; Mulawardhana , Pungky (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Encouraging early detection and prompt treatment of precancerous lesions is the key to preventing cervical cancer in women who are fertile. IVA examinations are used to detect precancerous lesions early on. Thus far, both nationally and at Mojo Health Center, the IVA examination has been achieved. Women of reproductive age may not be as aware of early diagnosis of precancerous lesions as they should be, which could contribute to the low IVA examination achievement. Due to a lack of understanding regarding the early diagnosis of precancerous lesions, women of reproductive age have low awareness. Method: A lecture and leafleting approach were used to conduct this health counseling. This kind of study uses a quasi-experimental pretest-posttest one group design, which is experimental in nature. carried out in Surabaya City at the Mojo Health Center. A straightforward random sampling methodology was used to choose the sample of 84 WUS, who were then split into two groups: the treatment group, which received an intervention counseling lecture style, and the control group, which received a leaflet intervention. A questionnaire was utilized to collect the data, and the Wilcoxon signed rank test was used to evaluate it. Independent Samples Test (p<0.05) and Wilcoxon signed Rank test. Results: The test results showing variations in both groups' knowledge levels produced the result p = 0.000 (p <0.05). P = 0.268 (p>0.05) was the outcome of the test to determine the value of differences in knowledge factors between the treatment group and the control group. Conclusion: There is no difference in WUS knowledge between the lecture method and leaflet media distribution when it comes to counseling, but there is a shift in the outcomes of WUS knowledge about early detection of cervical cancer before and after receiving counseling.